Regional and Distant Metastasis of Oral Squamous Cell Carcinoma in a Male Castrated Llama: A Case Report. (December 2021) - Kretsch, Cileah M.; Simpson, Katharine M.; Rawlinson, Jennifer E.; Laurence, Hannah; Spraker, Terry R.
A 19-year-old male castrated llama presented with a 3-year history of tooth root abscesses and an osseous mass on the left mandible. Surgical excision of the affected teeth and mass was performed, and histopathologic review indicated that the mass was an oral squamous cell carcinoma. The patient was admitted to the hospital again 4 months later in severe respiratory distress with submandibular edema, and bicavitary effusion. Necropsy results revealed regional and distant metastatic squamous cell carcinoma.